Ultra-performance supercritical fluid chromatography: A powerful tool for the enantioseparation of thermotropic fluorinated liquid crystals - Vaňkátová, Petra; Kalíková, Květa; Kubíčková, Anna (Analytica chimica acta, 2018)
A fast and simple supercritical fluid chromatography method for the enantioseparation of twenty newly synthesized orthoconic antiferroelectric liquid crystals is reported for the first time. The effects of alkoxy spacer length and fluorine atom presence and position in the phenyl ring on chromatographic behavior were investigated. Baseline enantioseparation of all compounds was achieved using simple mobile phases consisting of carbon dioxide and alcohol as cosolvent on (3,5-dimethylphenylcarbamate) derivative of amylose as chiral stationary phase. The analysis times ranged from 2 to 4 and from 4 to 7 min for most samples when using methanol and propane-2-ol, respectively. The significant effect of cosolvent type on the enantioseparation of these compounds was assessed and partial complementarity of methanol and propane-2-ol was observed.
Keywords: Supercritical fluid chromatography; Chiral fluorinated liquid crystals; Amylose; Liquid crystalline materials; Enantioseparation